THE EXISTING ROLES OF LITERACY TEACHERS IN THE ERA OF MULTILITERACIES: A SOCIOCULTURAL PERSPECTIVES - Rama Dwika Herdiawan (Journal of English Language Learning, 2021)
Abstract. Literacy is defined traditonally as ‘the  ability  to  read  and  write’  and it is also regarded as the ability to understand every single iinformation in different contexts or fields. Nevertheless,  the  new  literacy  approach  in the point of view of  the  post-structuralism  covers  the  representation of   texts  in  context,  different values,  meanings  and  the  principles  of  multiliteracies.  Traditional and modern concepts of literacy have correlation with a number of sociocultural activities which occurs in the in the society as well as the classroom which represents a social space. This study focuses on explaining the term  literacy  and  multiliteracies  in  the  postmodern  world  and  also  the existing roles  of  literacy  teachers  for  the  practical activities  in  Indonesian literacy classrooms. Keywords: Literacy Teachers, Multiliteracies, Sociocultural Perspectives